Buku ajar kehamilan untuk mahasiswa dan praktisi keperawatan serta kebidanan / Nurul Kamariyah, Yasi Anggasari, Siti Muflihah - NURUL KAMARIYAH, 1970-; Yasi Anggasari; Yasi Anggasari; Siti Muflihah (Salemba Medika, 2014)
x, 80 [74] hlm. : ilus. ; 21 cm [3 eks.]